Siyezwa ngabantu: listerning to the approches of a group of traditional healers towards hearing impairment. - De Andrade, Victor Manuel (My University, 2014)
Many South Africans consult with traditional healers in order to receive treatment for a variety of problems. Traditional and modem medicine have different views on disease which may cause disagreement between the two approaches. After interviewing a group of traditional healers, information was acquired regarding their beliefs on the aetiology, diagnosis and treatment of hearing impairment as well as information on their training, the perceived reasons for patients consulting with them,and potential for collaboration with modem medical practitioners. Consequently, it was found that different belief systems and world-views from those held by modem health care practitioners tended to guide this group of traditional healers in addressing hearing problems. However, despite these differences, similarities between the two approaches were also identified. The results of this study have important implications for audiologists and other modem health care professionals, policy makers, and traditional healers in terms of: cross-natural consultations; the possibility of sharing information regarding the effects of hearing impairment; the potential for collaboration with traditional healers; the potential use of traditional healers in primary health care; traditional healers as possible community educators; the potential use of traditional healers in identifying hearing impairment; the potential for the standardisation of traditional healers’ methods; and, further research